Factors contributing to mathematics performance of UiTM Johor Students / Masyfu’ah Mokhtar... [et al.] - Mokhtar, Masyfu’ah; Ghazali, Nurdia Azlin; Yusop, Haslenda; Nordin, Nur Syahidah (UiTM Cawangan Johor, 2019)
Some Mathematics courses offered by the Faculty of Computer Science and Mathematics (FSKM), University Technology MARA (UiTM) Johor, such as Pre-Calculus (MAT133), Calculus I (MAT183) and Calculus II (MAT233), have been identified as high failure rate courses for recent semesters. As considered by the top management of UiTM Johor, a high failure rate course is a course with more than 25% failure rate among the students who enrolled in the course. The performance of students in these Mathematics courses is a priority to the university management as it aims to produce quality students that can graduate on time. Thus, this study investigates the factors that contribute to the students’ Mathematics performance at UiTM Johor. A set of questionnaire was distributed to all students who enrolled in these courses. Descriptive analysis was conducted to analyse the demographic background of the respondents. The main analysis used Logistic Linear Regression to find out the most significant factors contributing to Mathematics performance. From the findings, SPM Additional Mathematics grades and class size were found to have significant influence on Mathematics performance of the students.